PEG-Modified tert-Octylcalix[8]arenes as Drug Delivery Nanocarriers of Silibinin - Desislava Budurova; Denitsa Momekova; Georgi Momekov; Pavletta Shestakova; Hristo Penchev; Stanislav Rangelov (MDPI AG, 2021)
The hepatoprotective properties of silibinin, as well its therapeutic potential as an anticancer and chemo-preventive agent, have failed to progress towards clinical development and commercialization due to this material's unfavorable pharmacokinetics and physicochemical properties, low aqueous solubility, and chemical instability. The present contribution is focused on the feasibility of using PEGylated calixarene, in particular polyoxyethylene-derivatized tert-octylcalix[8]arene, to prepare various platforms for the delivery of silibinin, such as inclusion complexes and supramolecular aggregates thereof. The inclusion complex is characterized by various instrumental methods. At concentrations exceeding the critical micellization concentration of PEGylated calixarene, the tremendous solubility increment of silibinin is attributed to the additional solubilization and hydrophobic non-covalent interactions of the drug with supramolecular aggregates. PEG-modified tert-octylcalix[8]arenes, used as drug delivery carriers for silibinin, were additionally investigated for cytotoxicity against human tumor cell lines.